Effect of melatonin supplementation on tinnitus: systematic literature review and meta-analysis: Melatonin and Tinnitus - Nocini, Riccardo; Henry, Brandon Micheal; Lippi, Giuseppe; Mattiuzzi, Camilla (Acta Biomedica Atenei Parmensis, 2024)
Background and aim. Because melatonin exerts a number of otoprotective effects, we planned a systematic literature review and meta-analysis to determine the potential effect of melatonin supplementation in reducing the severity of tinnitus disability. Methods: An electronic search of Scopus and Medline (PubMed interface) was performed using the keywords "tinnitus" AND "melatonin" without language or time restrictions. All clinical trials that examined the effect of melatonin supplementation on perceived severity of disability in tinnitus patients were identified. We finally included interventional, prospective studies that used the validated Tinnitus Handicap Inventory (THI) to assess disability. Results: The digital search yielded 104 articles, of which 98 were excluded because they did not meet inclusion criteria. Six studies (n=176 patients) were ultimately included in our analysis. In all studies, the weighted mean difference (WMD) of THI after melatonin supplementation was negative, with mean THI changes ranging from -2.5 to -19.5. The WMD of THI was -12.5 (95%CI, from -18.5 to -6.5; p=0.005; I2=71%). Conclusions: The findings of this comprehensive review and meta-analysis reveal that melatonin supplementation may have a positive influence on tinnitus disability and overall quality of life.